Determining factor that influences job performance amongst employees in oil palm plantation at Syarikat Ladang Dafa Estate / Norita Ali, Muhammad Faris Mehdin & Siti Norizyanti Harun - Ali, Norita; Mehdin, Muhammad Faris; Harun, Siti Norizyanti (2021)
This research is carried to determine the factors affecting employee firm output in oil palm plantation under the management of the Syarikat Ladang Dafa Sdn Bhd. The analysis purpose for: (a) to determine between recognition influences the work performance of the employees of the plantation; (b) to determine between compensation influences the work performance of the employees; and ( c) to determine between the work environment influences the employees' work performance. These objectives of research and survey was doing in the palm oil plantations at rural area nearby Kampung Biawak Lundu Kuching Sarawak, 250 employees were selected by using random sampling technique. Doing in the best practice and patients, the researchers collected data through a questionnaire that explored different characteristic the employees of job performance. The data analysis showed that recognition, pay, and work climate were important for deciding whether employees' output on the palm-oil plantation job would be high or poor. The discrepancies between the employees' pay, working environment, role fulfilment and recognition in their job performance is found to be high